PENINGKATAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI MELALUI MEDIA AUDIOVISUAL PADA KELAS VIII UPT SMP NEGERI 27 MEDAN - Larassati, Siti; Isman, Muhammad; Asiani, Aisyah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to improve the writing skills of observation report texts among eighth-grade students of SMPN 27 Medan for the 2024/2025 academic year through the application of audio-visual media. This classroom action research (CAR) is conducted in two cycles. Planning, implementation, observation, and reflection are the four stages that make up each cycle. 32 students from class VIII-6 were involved in this research. To measure the improvement in students' writing skills and their responses to the use of audio-visual media in learning, observation sheets, written tests, questionnaires, and interviews were used as data collection tools. The research results show that the use of audio-visual media can significantly enhance students' ability to write report texts based on what they observe. The percentage of student learning completeness in cycle I reached 57.6 percent with an average of 71.40, and in cycle II it increased to 87.5 percent with an average of 88.28. In addition, students' skills in organizing ideas, using appropriate language, and explaining observation results have improved.